Pengaruh Minum Air Putih terhadap Hasil Pemeriksaan Mikroskopis (Sedimen) Urin - Prasetyorini, Tri; Purwanti , Angki; Djayaningrat, Husyain; Putri, Tasha Dwisarah (Jurnal Kesehatan Cendikia Jenius, 2024)
Chronic Kidney Disease (CKD) is a kidney disorder characterized by abnormalities in kidney structure or function. Based on research results, cases of kidney failure experienced by adults are caused by kidney stones and urinary tract infections which can be caused by foods containing purine, drinking water containing hard water, frequent holding in urination and lack of fluids in the body which can result in dehydration. The aim of this study was to determine whether or not there was an effect of drinking water on urine sediment examination. This research was conducted at the Matraman Community Health Center, the research design in this study was Pre-Experimental, namely a study by carrying out experimental activities to determine the effect of drinking water on the results of microscopic examination (sediment) of urine by providing 2 liters of water or minerals/day once. administered before and after drinking water. This study used the Federer formula with 35 respondents and the results showed no significant differences between urine sediment examination before and after administering 2 liters of water, except for calcium oxalate crystals and uric acid. In conclusion, drinking 2 liters of water for one day has no effect on the results of microscopic examination (sediment) of urine and there are no significant differences between urine sediment examination before and after giving 2 liters of water/day, except for calcium oxalate and uric acid crystals in urine. It is recommended that further research follow up on any factors (influences) that can influence the microscopic examination (sediment) of urine.